CITRA PERUSAHAAN, PENGGUNA DAN PRODUK TERHADAP LOYALITAS KONSUMEN PADA PERUSAHAAN PENERBANGAN - Yogi Ashari; Juanita Rahmafatyra; Lut Mafrudoh (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2017)
This research is done to find out the direct and indirect influences of corporate image, user image, and aviation product image towards consumers’ loyalty.  The samples used were gathered from 100 respondents coming from Facebook accounts that are linked to official aviations services accounts.  The result shows that the corporate image, user image and aviation product image influences towards consumers’ loyalty scale is 61.3% and has a significant effect. The scale is the result of the Trimming mode path analysis by eliminating one exogenous variable which has no significant effect; that is the corporate image. From the two variables which have significant effect to consumers’ loyalty, the product’s image has the biggest effect with 39.1% percentage.